A Continuous Gradient Colloidal Glass (Adv. Mater. 7/2023). Issue 7 (19th February 2023) - Schöttle, Marius; Lauster, Tobias; Roemling, Lukas J.; Vogel, Nicolas; Retsch, Markus
Abstract : Photonic Colloidal Glass Continuous gradients in self‐assembled materials can provide functionality exceeding that of the homogenous case. In article number 2208745, Markus Retsch and co‐workers present a synthesis method that provides gradient size distributions via a controlled extraction emulsion process (CrEEP). The high degree of control allows the fabrication of a continuous‐gradient photonic glass with enhanced broadband reflectance.